2023
DOI: 10.3390/diagnostics13162627
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ruptured Intracranial Aneurysms Identification Using Different Machine Learning Algorithms and Radiomics

Abstract: Different machine learning algorithms have different characteristics and applicability. This study aims to predict ruptured intracranial aneurysms by radiomics models based on different machine learning algorithms and evaluate their differences in the same data condition. A total of 576 patients with intracranial aneurysms (192 ruptured and 384 unruptured intracranial aneurysms) from two institutions are included and randomly divided into training and validation cohorts in a ratio of 7:3. Of the 107 radiomics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, a study by Ludwig et al ( 33 ) found that radiomics-derived morphological features extracted from DSA did not significantly enhance the predictive performance for aneurysm rupture, contradicting Liu’s assertion that flatness is the most critical morphological determinant for predicting aneurysm stability. Yang et al ( 34 ) utilized radiomics features to distinguish between ruptured and unruptured intracranial aneurysms in the middle cerebral artery, constructing classification models with 12 common machine learning algorithms. The models built on AdaBoost, XGBoost, and CatBoost algorithms outperformed others, with AUCs of 0.889, 0.883, and 0.864, respectively.…”
Section: Applicationsmentioning
confidence: 99%
“…However, a study by Ludwig et al ( 33 ) found that radiomics-derived morphological features extracted from DSA did not significantly enhance the predictive performance for aneurysm rupture, contradicting Liu’s assertion that flatness is the most critical morphological determinant for predicting aneurysm stability. Yang et al ( 34 ) utilized radiomics features to distinguish between ruptured and unruptured intracranial aneurysms in the middle cerebral artery, constructing classification models with 12 common machine learning algorithms. The models built on AdaBoost, XGBoost, and CatBoost algorithms outperformed others, with AUCs of 0.889, 0.883, and 0.864, respectively.…”
Section: Applicationsmentioning
confidence: 99%
“…CatBoost uses a sequential boosting method that considers the order of categorical variables during the boosting process. In addition, it uses symmetric decision trees to improve generalization performance and includes various techniques to optimize sequencing in the learning process [22,23].…”
Section: Algorithms Used For Bc Metastasis Predictionmentioning
confidence: 99%